Lower extremity joint moments in athletics curve sprinting - Viellehner, J.; Heinrich, K.; Funken, J.; Alt, T.; Potthast, W. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to identify the effect of curve sprinting on the three dimensional joint kinetics and to specify the leg specific loading and functionality in the curve. Six male sprinters performed three submaximal curved and linear sprints. The findings point up different functionalities of the inner and outer leg. Peak knee and hip adduction moments were about twice as high at the inner leg compared to the outer leg during curve sprinting and compared to linear sprinting. Furthermore significantly higher peak external rotation moments in the knee and hip joints could be found during curve sprinting. In maximal sprinting these additional tasks may compromise propulsive force generation. These findings help to quantify the side specific load and provide information about involved muscles, which is helpful for the training process and injury prevention.